An Experimental Validation of Collision-Free Trajectories for Parallel Manipulators - Carbone, G.; Gómez-Bravo, F.; Selvi, Özgün (Taylor and Francis Ltd., 2012)
This article proposes a systematic approach for validating the trajectories generated by a motion planning method in presence of obstacles for parallel manipulators having less than 6 degrees of freedom (d.o.f.s). The planning algorithm is based on combining a quick random search algorithm together with an optimization method, which aims to obtain feasible and reliable trajectories. The validation approach uses a probabilistic method, which includes Kalman filtering of experimental data. Experimental tests have been carried out by operating a Cassino Parallel Manipulator (CaPaMan) prototype at LARM in Cassino. Results are reported and discussed to show the effectiveness of the proposed approach to generate and validate suitable collision-free trajectories for parallel manipulators. © 2012 Taylor & Francis Group, LLC.
Keywords: Trajectories; Parallel manipulators motion planning; Validation approach; Probabilistic methods